2011
DOI: 10.1007/s12253-011-9363-1
|View full text |Cite
|
Sign up to set email alerts
|

B-Raf Mutations, Microsatellite Instability and p53 Protein Expression in Sporadic Basal Cell Carcinomas

Abstract: Basal Cell Carcinoma (BCC) is the most common skin malignancy. Genes related to the Ras/Raf signalling pathway have been implicated in the pathogenesis of skin cancer. The objective of this study was to investigate the presence of B-Raf mutations in sporadic BCCs as well as its correlation with the phenotype of microsatellite instability (MSI), the clinicopathological parameters of the tumours and p53 protein expression. 83 BCC specimens were screened for B-Raf mutations, applying polymerase chain reaction, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In our study, most cBCCs overexpressed the p53 protein (60.5%), a frequency higher than the 45% found by Stamatelli et al 23 but similar to the values observed by Haghighi et al 24 ; both authors used the ≥ 10% cut-off to consider p53 positive expression. No associations were found between p53 overexpression and the clinical and histological features of the cBCCs, except for necrosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, most cBCCs overexpressed the p53 protein (60.5%), a frequency higher than the 45% found by Stamatelli et al 23 but similar to the values observed by Haghighi et al 24 ; both authors used the ≥ 10% cut-off to consider p53 positive expression. No associations were found between p53 overexpression and the clinical and histological features of the cBCCs, except for necrosis.…”
Section: Discussionsupporting
confidence: 90%
“…The scoring of tumors was done as follows: staining < 10% of tumor cells were considered as negative, and staining ≥ 10% was considered as positive 23 , 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The L597L (c.1791 A>T) mutation was found in a 47-year women with papillart thyroide carcinoma. This mutation was reported previously in one over 83 Basal cell carcinomas of the skin (Stamatelli et al, 2011) and it was considered as pathogenic in COSMIC (score 0.95)…”
Section: Discussionmentioning
confidence: 57%